The Legal Implication of Home-Based Worker’s Wage Regulation in Indonesia Prespective Pancasila - Flambonita, Suci; Rachmat Budiono, Abdul; Permadi, Iwan; Madjid, Abdul (Opción, 2019)
This research is titled “Maintaining the Use of Sundanese Language in Wayang Golek Performances in Bandung Regency, West Java, Indonesia”. The aim of this research is to explain the methods for maintaining the use of Sundanese language in Wayang Golek performances in the Bandung Regency (henceforth referred to as ‘Kabupaten Bandung’, West Java, Indonesia) and explain the factors that influence them. The method used in this research is the qualitative-descriptive method. The data sources are traditional wayang golek performances in Kabupaten Bandung, West Java. The results of this research show that 1) the methods for maintaning the use of Sundanese language in wayang golek performances include murwa, nyan- dra, antawacana, and tembang, 2) the factors that influence the insistence of main- taining the usage of Sundanese language are (a) to preserve cultural identity, (b) the spatial aspect of the performance; the region where the performance is held, and (c) the aesthetic aspect of the performance.